Patron’s Day 2003 (Institutional Knowledge at Singapore Management University, 2003)
Student performance at Singapore Management University's Patron's Day celebrations at the Bukit Timah campus on 20 January 2003. The banner behind the performers announces OnTrac, an online career services tool, which was launched to help students prepare for their job searches.